PATHOGENESIS OF MOUSE BRAIN FRONTAL CORTEX DAMAGE iN THE BACKGROUND OF SEASONAL INFLUENZA VIRUS A/H1N1 INFECTION - A. V. Kovner; O. G. Kurskaya; A. M. Shestopalov (Сибирский научный медицинский журнал, 2019)
In addition to the respiratory tract damage, an acute viral infection caused by the influenza A virus in the human body can cause central nervous system damage. Based on previous studies suggesting that the highly pathogenic influenza virus A/H5N1 A/Goose/Krasnoozerskoye/627/05 is neurotropic and induces inflammation in the central nervous system, the neurotropic and proinflammatory potential of seasonal influenza virus A/H1N1 A/Tomsk/13/2010 was studied on the mouse model. Material and methods. Work was carried out on the 2 month male mice BALB/c line divided into two groups – intact (5 animals) and intranasal infected with influenza A/H1N1 A/Tomsk/13/2010 dose of 1 MLD50 (20 animals for virological and 35 animals for histological studies). Viral titration obtained from the homogenates of lungs and brain was performed on MDCK cells, calculated by the method of Kerber in the modification of Ashmarin and expressed in lgTCID50 /ml. Histological studies included an immunohistochemical analysis of the lungs and the brain to detect influenza virus, markers of inflammation and tissue repair, as well as a morphological analysis of destructive changes in the tissues of the brain frontal cortex. Results and discussion. It was shown for the first time that the seasonal influenza A/H1N1 virus A/Tomsk/13/2010 does not have neurotropic potential. Simulation of influenza infection using the selected strain causes damage to the brain frontal cortex, which is expressed by perivascular and pericellular edema, small foci of hemorrhages and gliocytosis. Infection of BALB/c mice with a selected strain of influenza A virus causes activation of microglial cells of the frontal cerebral cortex. At the same time, the classical change of the phenotype from M1 to M2 does not occur, in the late days of the experiment (21–30) the proinflammatory classical phenotype prevails.